Nature, origin and evolution of a Late Pleistocene incised valley‐fill, Sunda Shelf, Southeast Asia. Issue 4 (17th April 2015) - Alqahtani, Faisal A.; Johnson, Howard D.; Jackson, Christopher A.‐L.; Som, Mohd Rapi B.
Abstract Understanding the stratigraphic fill and reconstructing the palaeo‐hydrology of incised valleys can help to constrain those factors that controlled their origin, evolution and regional significance. This condition is addressed through the analysis of a large (up to 18 km wide by 80 m deep) and exceptionally well‐imaged Late Pleistocene incised valley from the Sunda Shelf (South China Sea) based on shallow three‐dimensional seismic data from a large (11 500 km2), 'merge' survey, supplemented with site survey data (boreholes and seismic). This approach has enabled the characterization of the planform geometry, cross‐sectional area and internal stratigraphic architecture, which together allow reconstruction of the palaeo‐hydrology. The valley‐fill displays five notable stratigraphic features: (i) it is considerably larger than other seismically resolvable channel forms and can be traced for at least 180 km along its length; (ii) it is located in the axial part of the Malay Basin; (iii) the youngest part of the valley‐fill is dominated by a large (600 m wide and 23 m deep), high‐sinuosity channel, with well‐developed lateral accretion surfaces; (iv) the immediately adjacent interfluves contain much smaller, dendritic channel systems, which resemble tributaries that drained into the larger incised valley system; and (v) a ca 16 m thick, shell‐bearing, Holocene clay caps the valley‐fill. The dimension, basin location and palaeo‐hydrology of this incised valley leads to the conclusion that it represents the trunk river, which flowed along the length of the Malay Basin; it connected the Gulf of Thailand in the north with the South China Sea in the south‐east. The length of the river system (>1200 km long) enables examination of the upstream to downstream controls on the evolution of the incised valley, including sea‐level, climate and tectonics. The valley size, orientation and palaeo‐hydrology suggest close interaction between the regional tectonic framework, low‐angle shelf physiography and a humid‐tropical climatic setting.